Enhancing Pre-Service Science Teachers’ Pedagogical Content Knowledge through ICT-Mediated Microteaching: A University-Based Intervention - Damar Rais; Zhang Juan; Hamdi Thaib (Lembaga Yasin AlSys, 2026)
The development of pedagogical content knowledge (PCK) remains a major challenge in pre-service mathematics teacher education, particularly when they are required to connect content mastery, students’ learning difficulties, assessment, and technology-based learning. This study aims to analyze the effectiveness of information and communication technology (ICT)-assisted microteaching in strengthening pre-service mathematics teachers’ PCK and technological pedagogical content knowledge (TPACK) through a university-based intervention model. This study used a one-group mixed-methods design with a pretest-posttest, involving 32 pre-service mathematics teachers enrolled in a microteaching course. The intervention was implemented over eight weeks through ICT orientation, collaborative lesson planning, video-recorded microteaching, peer and instructor feedback, and reflective revision. Quantitative data were analyzed using descriptive statistics, paired-sample t-tests, 95% confidence intervals, and Cohen’s dz, while reflection notes and peer-feedback forms were analyzed thematically. The synthetic data used in this manuscript showed substantial increases in PCK rubric scores from 63.70 to 77.62, TPACK self-efficacy from 3.22 to 3.91, ICT self-efficacy from 3.03 to 3.71, and microteaching performance from 67.29 to 80.83. The greatest improvement occurred in the ICT-based representation domain, followed by instructional strategies and diagnosis of students’ misconceptions. The qualitative findings showed that video-assisted peer feedback helped participants identify mismatches between content and pedagogy, refine instructional representations, and design formative assessment more effectively. This study shows that structured ICT-assisted microteaching can serve as a practical bridge between PCK development and technology integration in pre-service mathematics teacher education at the higher education level.